Systematic Review of Fish Ecology and Anthropogenic Impacts in South American Estuaries: Setting Priorities for Ecosystem Conservation - Barletta, Mário; Lima, André R. A. (Frontiers in Marine Science, 2019)
Research on estuarine ecology in South America (SA) increased quali-quantitatively since the early 1980 in search of consistent recommendations for estuarine conservation. The most important ecological theory achieved is that the seasonal fluctuation of the salinity gradient creates an ecocline influenced by gradual changes between river-dominated to marine-like waters. Estuarine fish fauna adapts to these changeable abiotic characteristics, including the spatial and seasonal bioavailability of dissolved oxygen and numerous pollutants. However, studies on the influence of the estuarine ecocline are still missing for key estuarine systems. This study provides an overview of fish ecology and anthropogenic impacts within estuarine systems of SA and discusses priorities for environmental conservation. Research on fish reached important conclusions regarding essential habitats and fish interaction with other biological and abiotic compartments over spatio-temporal settings, including conditions of severe anthropogenic impacts. These impacts are related to unplanned urban settlements, industrial estates, ports, damming of major rivers, dredging activities and deforestation for extensive farming. Changes in estuarine morphology alter natural flows and lead to habitat losses, disrupting the ecocline and impairing fishes from moving among formerly connected habitats, especially earlier ontogenetic phases. In addition, industrial, urban and farming activities often result in high loads of metals and persistent organic pollutants, organic enrichment and oxygen depletion. Moreover, plastic debris, a ubiquitous contaminant with sources on every human activity, including fishing, when fragmented into microplastics, become preferably concentrated in semi-enclosed environments, as estuaries. Metals, POPs and microplastics are actually asserted to be persistent. When in high concentrations, they become bioavailable to the estuarine trophic web through bioaccumulation, being biomagnified or biotransfered towards higher trophic level organisms, such as top predator fishes. Therefore, research on environmental quality and fish ecology must be based on robust sampling designs along the whole ecocline using long-term approaches. In addition, basic sanitation, co-management, an improved licensing system and scientifically-based risk assessments/monitoring for all sorts of enterprise are also urgent. These conservation priorities need to be in place before human-driven changes surpass the ecosystem’s capacity to produce resources and maintain services.